What you get is what you need? The role of venture capitalists in managing growth of new ventures - Ann-Kristin Achleitner; Christian H. Fingerle (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2004)
The resource-based view is suggested as a useful concept to shed light on the particular challenges of high potential companies on their way to building a thriving and growing company. In order to be able to apply the theoretical constructs of the resource-based view in the present context, a categorization of resources is elaborated that fits particularly well to high potential companies. Existing literature provides evidence that these companies in general only dispose of a small resource base and that they are characterized by strong resource needs in all relevant resource categories. The role of venture capitalists is assumed to provide high potential companies with financial and non-financial resources that help to create core and non-core competencies. Ultimately, this bundle of core and non-core competencies would allow high potential companies to achieve a sustained competitive advantage. The empirical results of this paper are based on insights from three in-depth case studies on German start-ups, each representing a different investor-investee dyad. It comprises investees from different industries such as software, biotech, and energy as well as investors with an established track record, first fund investors, and semi-government-dependent investors. The cases show that venture capitalists provide a number of resources to their portfolio companies that allow building a competitive advantage. The role of the venture capitalists is thus to help high potential companies to complement existing resources and competences in order to develop their full economic potential. However, there is great variation between the resource provisions of the analyzed venture capital firms.
Keywords: M13; G29; 330; Entrepreneurship; Venture Capital; Resource-based View